PENGARUH BUDAYA ORGANISASI, KOMITMEN ORGANISASI, DAN KOMPENSASI TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (STUDI PADA DINAS KESEHATAN DAERAH KOTA TOMOHON) - Stefanie Inggrid Gorap; Siti Haerani; Wardhani Hakim (Hasanuddin Journal of Applied Business and Entrepreneurship, 2019)
Human resources are the most important asset for an organization because of its role as the subject of organizational policy and operational activities. This study aims to determine to determine the influence of organizational culture, organizational commitment, and compensation on employee performance through job satisfaction at the District Health Office Tomohon City. This study explains the influence and influence of the variables to be studied. Using a quantitative approach because the data used to analyze the relationship between variables is expressed by numerical scaling or scale. Test results have been done indicate that organizational culture has a significant effect on employee performance, organizational commitment has a significant effect on employee performance, compensation has a significant effect on employee performance, job satisfaction has a significant effect on the performance of pegawaI. Simultaneously organizational culture, organizational commitment, compensation and job satisfaction will have an effect on the performance of employees at the District Health Office Tomohon.